Gels for Oil and Gas Industry Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue includes many advanced high-quality papers that focus on gel applications in the oil and gas industry. The papers in this Special Issue present the new development of gels that can be used as conformance control agents, drilling fluid additives, and hydraulic fracturing agents.